Correlation of immunohistochemical mismatch repair protein status between colorectal carcinoma endoscopic biopsy and resection specimens. Issue 7 (1st February 2018) - O'Brien, Odharnaith; Ryan, Éanna; Creavin, Ben; Kelly, Michael E; Mohan, Helen M; Geraghty, Robert; Winter, Des C; Sheahan, Kieran
Abstract : Background: Microsatellite instability is reflective of a deficient mismatch repair system (dMMR), which may be due to either sporadic or germline mutations in the relevant mismatch repair (MMR) gene. MMR status is frequently determined by immunohistochemistry (IHC) for mismatch repair proteins (MMRPs) on colorectal cancer (CRC) resection specimens. However, IHC testing performed on endoscopic biopsy may be as reliable as that performed on surgical resections. Aim: We aimed to evaluate the reliability of MMR IHC staining on preoperative CRC endoscopic biopsies compared with matched-surgical resection specimens. Methods: A retrospective search of our institution's histopathology electronic database was performed. Patients with CRC who had MMR IHC performed on both their preoperative endoscopic biopsy and subsequent resection from January 2010 to January 2016 were included. Concordance of MMR staining between biopsy and resection specimens was assessed. Results: From 2000 to 2016, 53 patients had MMR IHC performed on both their preoperative colorectal endoscopic biopsy and resection specimens; 10 patients (18.87%) demonstrated loss of ≥1 MMRP on their initial endoscopic tumour biopsy. The remainder (81.13%) showed preservation of staining for all MMRPs. There was complete agreement in MMR IHC status between the preoperative endoscopic biopsies and corresponding resection specimens in all cases (κ=1.000, P<0.000) with a sensitivity of 100% (95% CI 69.15 to 100) and specificity of 100% (95% CI 91.78 to 100) for detection of dMMR. Conclusion: Endoscopic biopsies are a suitable source of tissue for MMR IHC analysis. This may provide a number of advantages to both patients and clinicians in the management of CRC.